Association between tea consumption and stroke in the American adult females: analyses of NHANES 2011–2018 data - Miao, Yongyue; Ma, Sijia; Wu, Xian (Frontiers in Nutrition, 2024)
Background: Epidemiological surveys show that there is a significant gender difference in the incidence of stroke, with females having a noticeably higher rate than males. Accordingly, it is crucial to seek preventive measures for stroke specifically targeted at females. Although previous studies have shown that tea has been proven to be negatively correlated with stroke, the relationship between tea and stroke in American adult females is still unclear. Therefore, we aimed to investigate the relationship between tea consumption and the occurrence of stroke in American adult females.Methods: The data analyzed is derived from the NHANES database between 2011 and 2018. The quantity of tea consumed was gathered from a 24-hour dietary review. Stroke was identified by using questionnaire. The association between tea consumption and stroke was investigated using a weighted regression model. Then we used interaction testing and subgroup analysis to conduct a thorough analysis. Simultaneously, the association between the sugar content in tea and stroke was examined.Results: This study included 5731 adult females aged between 20 and 60 years. Compared to those who did not consume tea, the likelihood of stroke decreased by 9% for each additional 100g of tea ingested by participants (OR=0.91, 95%CI: 0.83-1.00). In the unadjusted model, those who drank 307.5-480 g of tea per day had a substantially decreased risk of stroke than those who did not drink tea (OR=0.